Recent progress in microRNA detection using integrated electric fields and optical detection methods - Velmanickam, Logeeshan; Nawarathna, Dharmakeerthi (Frontiers in Lab on a Chip Technologies, 2024)
Low-cost, highly-sensitivity, and minimally invasive tests for the detection and monitoring of life-threatening diseases and disorders can reduce the worldwide disease burden. Despite a number of interdisciplinary research efforts, there are still challenges remaining to be addressed, so clinically significant amounts of relevant biomarkers in body fluids can be detected with low assay cost, high sensitivity, and speed at point-of-care settings. Although the conventional proteomic technologies have shown promise, their ability to detect all levels of disease progression from early to advanced stages is limited to a limited number of diseases. One potential avenue for early diagnosis is microRNA (miRNA). Due to their upstream positions in regulatory cascades, blood-based miRNAs are sensitive biomarkers that are detectable earlier than those targeted by other methods. Therefore, miRNA is a promising diagnostic biomarker for many diseases, including those lacking optimal diagnostic tools. Electric fields have been utilized to develop various biomedical assays including cell separation, molecules detection and analysis. Recently, there has been a great interest in the utility of electric fields with optical detection methods, including fluorescence and surface plasmons toward biomarker detection. This mini review first summarizes the recent development of miRNA as a biomarker. Second, the utility of electric fields and their integration with fluorescence detection methods will be discussed. Next, recent studies that utilized electric fields and optical detection methods will be discussed. Finally, in conclusion, technology gaps and improvements needed to enable low-cost and sensitive biomarker detection in point-of-care settings will be discussed.